A descriptive evaluation of causes of death in venovenous extracorporeal membrane oxygenation. (January 2023) - Dave, Sagar B; Deatrick, Kristopher B; Galvagno, Samuel M; Mazzeffi, Michael A; Kaczorowski, David J; Madathil, Ronson J; Rector, Raymond; Tabatabai, Ali; Haase, Daniel J; Herr, Daniel; Scalea, Thomas M; Menaker, Jay
Veno-venous extracorporeal membrane oxygenation (VV ECMO) has become an important support modality for patients with acute respiratory failure refractory to optimal medical therapy, such as low tidal volume mechanical ventilator support, early paralytic infusion, and early prone positioning. The objective of this cohort study was to investigate the causes and timing of in-hospital mortality in patients on VV ECMO. All patients, excluding trauma and bridge to lung transplant, admitted 8/2014–6/2019 to a specialty ICU for VV ECMO were reviewed. Two hundred twenty-five patients were included. In-hospital mortality was 24.4% ( n  = 55). Most non-survivors (46/55, 84%) died prior to lung recovery and decannulation from VV ECMO. Most common cause of death (COD) for patients who died on VV ECMO was removal of life sustaining therapy (LST) in setting of multisystem organ failure (MSOF) ( n  = 24). Nine patients died a median of 9 days [6, 11] after decannulation. Most common COD in these patients was palliative withdrawal of LST due to poor prognosis ( n  = 3). Non-survivors were older and had worse predictive mortality scores than survivors. We found that death in patients supported with VV ECMO in our study most often occurs prior to decannulation and lung recovery. This study demonstrated that the most common cause of death in patients supported with VV ECMO was removal of LST due MSOF. Acute hemorrhage (systemic or intracranial) was not found to be a common cause of death in our patient population.